PHYTOCHEMICAL ANALYSIS OF METHANOLIC EXTRACT OF ROOTS OF ASPARAGUS RACEMOSUS (Shatavari) - JAYASHREE G.V; RACHITHA P; KRUPASHREE K; HEMANTH KUMAR K; FARHATH KHANUM (International Journal of Pharma and Bio Sciences, 2013)
Asparagus racemosus (Asparagaceae) is one of the most frequently used herb in Indian traditional medicine. The objective of the present study was, phytochemical screening of methanolic extract of roots of A. racemosus. The collected roots were washed, shade dried, powdered and stored in air tight container. The dried powdered material was extracted with methanol. One kg of powder was immersed in methanol solution in a flat bottom flask. The extract was concentrated to dryness under reduced pressure and controlled temperature using rotary flash evaporator. The yield of the methanolic extract was recorded as 9%. The phytochemical screening of A. racemosus was performed using generally accepted laboratory techniques for qualitative determinations. The analysis shows presence of phytosterols, triterpenoids, flavonoids, lactones, glycosides, fatty acids, phenolic compounds, saponins and tannins.